Shang-Chi by Gene Luen Yang. Vol. 1, Brothers & sisters - Yang, Gene Luen (Marvel Worldwide, Inc., 2021)
"THE MASTER RETURNS! An ancient and evil secret society has stayed in hiding since the death of their leader, Zheng Zhu. But now his successor has been chosen to shift the balance of power in the world... Zheng Zhu's son, Shang-Chi! Witness the Marvel Universe's greatest fighter return to a world of death and destruction he thought he left behind long ago... and discover the secrets to Shang-Chi's past that will change his world forever!"--Provided by publisher.